Supporting Siblings of Children with Cancer: A Need for Family–School Partnerships - Alderfer, Melissa A. (2010)
When a child has a chronic illness, it is readily apparent that the family and school must enter into a partnership to assure that the educational needs of the child are being met. A family–school partnership, however, may also be important to address the needs of siblings of children with chronic illness. Siblings of children with diseases such as cancer are often highly distressed and may experience decrements in academic achievement within 2 years of diagnosis. Teachers and classroom peers may be a valuable source of support to these children. This manuscript documents the mental health needs of siblings of children with cancer, describes their perceptions regarding amount of social support received and importance of social support across home and school sources, and reveals important associations between social support and more positive emotional, behavioral, and academic functioning. These findings suggest that family–school partnerships may be valuable to address the mental health needs of siblings of children with cancer.